Pharmaceutical development and standardization of Salvia stepposa tablets - Levaya, Y.; Badekova, K.; Atazhanova, G.; Ivasenko, S. (Fundamental and Experimental Biology, 2025)
In response to the growing threat of antimicrobial resistance, plant-derived compounds are increasingly being explored as safe and effective alternatives to conventional antibiotics. This study focused on the development of solid oral dosage forms based on a dry extract of Salvia stepposa (MVSHS-40), rich in phenolic acids and flavonoids with proven antimicrobial and anti-inflammatory activity. The extract was obtained using microwave-assisted extraction (MAE) with 40% ethanol, yielding up to 6% rosmarinic acid as the dominant bioactive compound, along with caffeic and p-coumaric acids, and flavonoids such as apigenin, naringenin, and luteolin. The tablets were formulated by direct compression using microcrystalline cellulose, EMDEX, citric acid, and calcium stearate, with some variants incorporating essential oils. Out of more than 30 experimental variants, five optimized compositions were selected. Physicochemical and pharmacopeial evaluations confirmed excellent disintegration times (<12 minutes), dissolution rates (>79%), uniform mass, high mechanical strength (≥107 N), and minimal friability (≥99.99%). HPLC-UV/MS analysis quantified 3.046 mg of rosmarinic acid per tablet. Comparative analysis revealed a 5.5-fold increase in active content over commercial Salvia officinalis tablets while avoiding thujone-related safety concerns. Stability studies over 18 months demonstrated sustained integrity of pharmacological properties. The resulting MVSHS-40 tablets meet all quality specifications and represent a safe, stable, and effective herbal formulation with potential applications in the prevention and treatment of upper respiratory tract infections.